Mental health during pregnancy among early and non-early married females - Gul, Nighat; Babar, Madiha; Niwaz, Asif; Alvi, Sajid Mehmood; Perveen, Shaghufta; Amir, Shireen; Shah, Syed Afzal; Yousafzai, Aziz ur Rehman (Pakistan Journal of Physiology, 2019)
Background: Pregnancy is a risk factor for mental health of women. Marriage at <18 years age falls in category of early marriage. This is an immature stage of life, thus particularly influence the pregnant female’s mental health more enormously than non-early married females. This study tried to compare mental health of early and non-early married females during pregnancy. Method: One hundred and fifty (150) early and non-early married pregnant women were included in the study by applying non-probability clinical sampling technique. There were 75 early married females and 75 non-early married females. Comparative descriptive research design was applied. The study was conducted from Jan to Sep 2017 at University of Haripur. Veit and Ware mental health scale of Mental Health Inventory-38 (MHI-38) was used for data collection. Results: Anxiety, depression, loss of behaviour, and psychological distress scores were higher (41.72±7.64, 17.19±3.08, 40.13±9.07 and 87.53±21.84 respectively) in early married females. Mean scores for emotional ties, general positive effect, life satisfaction, and psychological wellbeing in early married females were lower than non-early married females (10.59±1.75, 7.59±2.34, 2.36±7.99, and 23.75±8.11 respectively). Overall mental health was higher in non-early married pregnant females than early married females (276.52±30.15 vs 189.41±17.40). All findings were significant at p<0.001. Conclusion: Early married pregnant females’ mental health was found to be more disturbed during pregnancy than non-early married pregnant females.